2020
DOI: 10.1016/j.mtla.2019.100511
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer CdHgTe-based infrared detector: 2D/3D microtomography, synchrotron emission and finite element modelling with stress distribution at room temperature and 100 K

Abstract: The mechanical behaviour of a CdHgTe-based infrared detector was evaluated after processing at several temperatures to determine the impact of thermomechanical loading on residual stress and reliability. The architecture of the detector was first entirely characterized, relying on SEM, X-ray microtomography and diffraction analysis, in order to get the nature, the morphology and the crystallographic orientation of all the constitutive layers, and in particular the indium solder bumps. The results notably showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…For the stress results in HgCdTe, the value obtained with the nominal FEM model is 49 MPa: it is thus less influenced by elastic assumption and geometry simplification than warpage (even equation (10) led to a value only 9% higher). As expected from the analytical models, (apart from edge effects and stress concentration), the stress in HgCdTe is biaxial and homogeneous in x and y directions (Fig.…”
Section: Fem Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…For the stress results in HgCdTe, the value obtained with the nominal FEM model is 49 MPa: it is thus less influenced by elastic assumption and geometry simplification than warpage (even equation (10) led to a value only 9% higher). As expected from the analytical models, (apart from edge effects and stress concentration), the stress in HgCdTe is biaxial and homogeneous in x and y directions (Fig.…”
Section: Fem Resultsmentioning
confidence: 91%
“…Some XRD stress measurements in HgCdTe have already been published in literature, considering a simple epitaxial layer on a CdZnTe substrate [7,8] and an achieved IR detector [9,10]. For the epitaxy process, biaxial stress values were measured, mainly induced by imperfect lattice match between Hg 1-x Cd x Te and Cd 1-y Zn y Te.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that In bumps with tetragonal crystal structure are highly anisotropic in their thermomechanical behavior [27][28][29] . Lebaudy et al showed that the thermomechanical response of IR detector can yield notable variations due to random crystallographic orientations of the In bumps [30] .…”
Section: Discussionmentioning
confidence: 99%